Massive gastrointestinal haemorrhage from a duodenal diverticulum: a case report - Seneviratne, S.A.; Samarasekera, D.N. (My University, 2009)
Bleeding duodenal diverticulum is a rare cause of gastrointestinal bleeding, which sometimes can be massive and life threatening. We report one such case and the management, with a successful outcome. Different diagnostic techniques and management options available are also discussed.